Best thinking in business analytics from the Decision Sciences Institute - Warkentin, Merrill (Pearson Education, 2016)
Today, business success depends on making great decisions and making them fast. Leading organizations apply sophisticated business analytics tools and technologies to evaluate vast amounts of data, glean new insights, and increase both the speed and quality of decision making. In The Best Thinking and Practices in Business Analytics from the Decision Sciences Institute, DSI has compiled award-winning and award-nominated contributions from tis most recent conferences - papers that illuminate exceptionally high-value applications and research on analytics for decision making. Topics covered in this collection include: predicting customer response and demand behavior; optimizing the accuracy of credit scoring; forecasting stock index and gold prices; choosing suppliers, carriers, and facility locations; implementing more efficient transportation networks; and much more. These papers have appeared in no other DSI collection and offer exceptional value for all business, academic, and organizational professionals concerned with the science of decision making. Explore them here, and you'll discover powerful new opportunities for competitive advantage through analytics. -- from dust jacket.